Event-triggered distributed cross-dimensional formation control for heterogeneous multi-agent systems - Wei, Huimin; Peng, Chen; Zhao, Min (Frontiers of information technology & electronic engineering, 2024)
This paper concerns the event-triggered distributed cross-dimensional formation control problem of heterogeneous multi-agent systems (HMASs) subject to limited network resources. The central aim is to design an effective distributed formation control scheme that will achieve the desired formation control objectives even in the presence of restricted communication. Consequently, a multi-dimensional HMAS is first developed, where a group of agents are assigned to several subgroups based on their dimensions. Then, to mitigate the excessive consumption of communication resources, a cross-dimensional event-triggered communication mechanism is designed to reduce the information interaction among agents with different dimensions. Under the proposed event-based communication mechanism, the problem of HMAS cross-dimensional formation control is transformed into the asymptotic stability problem of a closed-loop error system. Furthermore, several stability criteria for designing a cross-dimensional formation control protocol and communication schedule are presented in an environment where there is no information interaction among follower agents. Finally, a simulation case study is provided to validate the effectiveness of the proposed formation control protocol.